Measurement of peripheral muscle oxygen saturation in conscious healthy horses using a near-infrared spectroscopy device. (November 2019) - Gingold, Benjamin MC.; Killos, Maria B.; Griffith, Emily; Posner, Lysa
Abstract: Objective: Maintaining adequate muscle tissue oxygenation is of paramount importance during equine general anesthesia. The objectives of this study were to assess the feasibility, reliability and repeatability of near-infrared spectroscopy (NIRS) muscle oximetry using the Inspectra m650 in conscious healthy adult horses. Study design: Prospective, observational study. Animals: A group of 30 healthy client-owned adult horses admitted to the equine hospital between July 2017 and July 2018. Methods: The probe of an Inspectra m650 NIRS tissue oximeter was placed on the hairless surface of five muscle sites (omotransversarius, triceps long head, extensor carpi ulnaris, vastus lateralis and lateral digital extensor) on the left side of the body of each standing, unsedated horse. Each site had muscle oxygenation (StO2 ) recordings measured in triplicate and statistical modeling used to assess the reading reliability and repeatability within and between muscle sites. Results: The readings acquired at the vastus lateralis and extensor carpi ulnaris muscle sites had highly repeatable values [mean (90% confidence interval): StO2, 95% (93.8%, 96.5%) and 93% (91.6%, 93.9%), respectively; intraclass correlation coefficients, 0.92 and 0.80, respectively]. These two sites also had high reliability (represented by the percentage of successful readings; 70% and 86%, respectively). Conclusions and clinical relevance: The use of NIRS muscle oxygenation technology is a clinically feasible means to assess tissue oxygenation in horses. The vastus lateralis and extensor carpi ulnaris muscle sites provided the most reliable and repeatable readings when using the Inspectra m650 machine in horses.